(untitled) (Proceeding of the International Conference on Arts and Humanities, 2022)
The fusion between Asian culture and western music has widely influenced Tazul’s compositional approaches. His influence from Malaysian poetry and gamelan music has been illustrated in his work Sebuah Pantun I. These influences have crafted a way of composing mediating Asian norms and western style which later he called ‘gamelbati’. This article presents a detailed analysis of the first movement of Sebuah Pantun for solo piano employing the numbering systems of gamelan songs and the format of four-line ‘pantun’. Sebuah Pantun for solo piano has four small subsections imitating the four-line ‘pantun’ which are two-line of ‘pembayang’ (shadow) and two-line meaning of the ‘pantun’. The imitation of gamelan pelog scale and the format of four-line pantun incorporating Western instruments, notation and style has work perfectly in this composition work. Tazul’s work also uses primarily five series of notes, but two extra notes were only used once throughout the piece. This suggests that the composer referred to the seven-tone of the pelog scale that was widely used in gamelan music. The composer uses serial composition as the main compositional approach in this work, where the notes are retrograded which then grouped to form several small sections imitating the four-line ‘pantun’. Using the gamelan songs’ numbering systems and four-line ‘pantun’ in his composition approach has explored the shape, space and musical aesthetic in an effective and imaginative way.